Macro and Micro Features of Successful Economic Convergence : The Case of Poland - Schiffbauer, Marc; Varela, Gonzalo (World Bank, Washington, DC, 2019)
This paper examines the patterns of growth of Poland, and its transition into high-income status over the past two decades from a macro and micro perspective. It benchmarks Polish performance with that observed in established high-income countries, and with that of others that have been trapped in middle--income levels and examines the role that integration into the EU had on growth. The analysis reveals, first, that Poland’s growth process has been accompanied by a process of diversification of assets, including institutions, physical and human capital. Second, that the progressive integration into the EU bloc boosted growth and productivity because of three keyfactors: (i) increased openness to trade, investment and talent, (ii) increased domestic competition, and regulatory harmonization with EU, (iii) increased certainty in reforms, through a commitment to EU-institutions. Third, that for full convergence to high-income levels, Polish firms need to increase their innovative capacities. The paper extracts lessons applicable to other economies trapped in middle-income levels, as well as to Poland itself to consolidate growth looking forward.